EFFECT OF COLCHICINE TREATMENT ON PLANT GROWTH AND FLOWER DEVELOPMENT IN Zinnia elegans - Kusumawati, Eni; Haryanto, Haryanto; Wijaya, Nur Iman; Alaudin, Ahmad Muzaki Nurrah-man; Nurhayati, Sari; Fitri, Fadillya Maulidilla (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Refugia is a flowering plant that is intended to trap and destroy insects. Colchicine is reported to induce polyploidy in plants. This study aims to determine germination, growth, and refugia performance of colchicine induced Zinnia elegans at different immersion concentrations and times. This research was conducted experimentally with a completely randomized design. The treatment was immersion in colchicine solution at different times duration. Colchicine concentration 0.01% with immersion time of 6,12,24,48, and 72 hours. Colchicine induction with different immersion times showed a decrease in sprouts height (p<0.05), resulting in abnormal sprouts with three leaves and wider leaf area (correlation test r=0.560). The longer the colchicine immersion showed plant height (correlation test r=0.618). Morphologically, control and colchicine induction results were relatively the same, but flowers resulting from colchicine induction had higher flower heights (correlation test r=0.772) and flower diameter (correlation test r=0.815). Induction of colchicine immersion had a different effect on the growth and reproduction performance of Z. elegans.